2013
DOI: 10.3109/0284186x.2013.813073
|View full text |Cite
|
Sign up to set email alerts
|

Reduced lung dose and improved inspiration level reproducibility in visually guided DIBH compared to audio coached EIG radiotherapy for breast cancer patients

Abstract: Introduction. Patients with left-sided breast cancer with lymph node involvement have routinely been treated with enhanced inspiration gating (EIG) for a decade at our institution. In a transition from EIG to deep inspiration breath hold (DIBH) we compared the two techniques with focus on target coverage, dose to organs at risk and reproducibility of the inspiration level (IL). Material and methods. Twenty-four patients were computed tomography (CT) scanned with EIG and DIBH. For DIBH we used visual feedback a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…Visual guidance with goggles or monitors improves the reproducibility of breath hold, as presented by Damkjaer et al [13,17]. Rong et al found that the RPM system alone is not sufficient to verify the BHL [18] and used three-dimensional (3D) surface imaging as a second method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual guidance with goggles or monitors improves the reproducibility of breath hold, as presented by Damkjaer et al [13,17]. Rong et al found that the RPM system alone is not sufficient to verify the BHL [18] and used three-dimensional (3D) surface imaging as a second method.…”
Section: Discussionmentioning
confidence: 99%
“…The marker block used can be placed either on the abdominal wall at the level of the diaphragm [5,6,12] or on bony sternum [8,13]. RPM measures the BHL only indirectly and in anterior-posterior (AP) dimension -thus the actual BHL must be re-verified in the treatment situation [9,10].…”
mentioning
confidence: 99%
“…For both respiratory gating in free breathing and breath-hold techniques, it has been shown that reproducibility and stability can be enhanced by use of patient training and coaching techniques, using both audio and visual guidance 33,34 (see the Decision making strategies for motion management section).…”
Section: Motion Management Strategiesmentioning
confidence: 99%
“…Increased lung volume in deep inspiration breath hold (DIBH) facilitates a potential for lung toxicity decrease [6,7]. DIBH RT has been successfully applied for a decade, primarily for breast cancer RT [8,9]. However, it is generally feared that lung cancer patients will have poorer lung function and a lower compliance.…”
Section: Supplementary Materials Available Onlinementioning
confidence: 99%